Math, asked by sammy3794, 1 year ago

Please answer this question​

Attachments:

Answers

Answered by aakansha00
1

2^m+4-2^ m +2=3

2^m(2^4-2^2)=3

2^m(12) =3

2^ m=1/4

2^m=(1/2)^2

Answered by tahseen619
1

 {2}^{m + 4}  -  {2}^{m  + 2}  = 3 \\  {2}^{m} . {2}^{4}  -  {2}^{m} . {2}^{2}  = 3 \\  {2}^{m} ( {2}^{4}  -  {2}^{2} ) = 3 \\  {2}^{m} (16 - 4) = 3 \\  {2}^{m} (12) = 3 \\   {2}^{m}  =  \frac{3}{12}  \\  {2}^{m}  =  \frac{1}{4}  \\  {2}^{m}  =  \frac{1}{ {2}^{2}  } \\  {2}^{m}  =  {2}^{ - 2}  \\ m =  - 2

Similar questions